PERKADERAN UPAYA MENCETAK KADER MUHAMMADIYAH YANG RESPONSIF DI SMKS AHLU SHUFFAH BANTAENG - Risman, Risman; Mukramin, Sam’un; Muslimin, Abdul Azis (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Moral degradation in the younger generation is one of the causes of social and religious deviation. The existence of the IPM organization as a forum for implementing interests and talents based on religious values. HDI cadre formation is a transformative effort to create a generation that has a formal cadre level that is in line with Muhammadiyah goals. Field research (field research) is a method of collecting data in qualitative research that does not require in-depth knowledge of the literature used and certain abilities on the part of the researcher. The place for carrying out cadre activities at the Ahlu Shuffah Islamic Boarding School, Bantaeng Regency. The target of this activity is equal students who are at the Ahlu Shuffah Islamic Boarding School, Bantaeng. The cadre process is an effort to realize the ideals, namely the formation of knowledgeable, noble, and skilled Muslim students in the context of upholding and upholding the values of Islamic teachings so that a true Islamic society is realized with the spirit of Fatabiqul khairat. This is in accordance with Azaki Khoirudin's theory that the IPM cadre system actually uses the tarbiyah and da'wah methods which are presented based on the facts on the ground capable of provoking the criticality of the participants in providing responsive and constructive ideas.